Hybrid Genetic Algorithm and Simulated Annealing for Function Optimization - Fatyanosa, Tirana Noor; Sihananto, Andreas Nugroho; Alfarisy, Gusti Ahmad Fanshuri; Burhan, M Shochibul; Mahmudy, Wayan Firdaus (Faculty of Computer Science (FILKOM) Brawijaya University, 2016)
The optimization problems on real-world usually have non-linear characteristics. Solving non-linear problems is time-consuming, thus heuristic approaches usually are being used to speed up the solution’s searching. Among of the heuristic-based algorithms, Genetic Algorithm (GA) and Simulated Annealing (SA) are two among most popular. The GA is powerful to get a nearly optimal solution on the broad searching area while SA is useful to looking for a solution in the narrow searching area. This study is comparing performance between GA, SA, and three types of Hybrid GA-SA to solve some non-linear optimization cases. The study shows that Hybrid GA-SA can enhance GA and SA to provide a better result